Analisis Faktor-Faktor yang Mempengaruhi Partisipasi Kerja Lansia di Kecamatan Mengwi Kabupaten Badung - Ni Kadek Yunisandra; Made Dwi Setyadhi Mustika (Journal Of Business, Finance, and Economics (JBFE), 2024)
The elderly population in developing countries in their youth generally had jobs in the informal sector, so that at the time their parents were still working diligently to be able to meet their daily needs. This research aims to carry out analyzes related to the influence of education level, health complaints, use of free time, family income and number of dependents simultaneously and partially, and is used to determine the variables that have a dominant influence. The population in this study was elderly people aged 60 years and over with data of 20,019 people by applying the Slovin Formula, resulting in 123 respondents. In carrying out the process of determining the number of samples, the non probability sampling method was used with Accidental Sampling and Snowball Sampling. In the data collection process, observation methods, structured interviews and in-depth interviews were used. The data analysis techniques used are descriptive analysis and multiple linear regression analysis. The results of the research successfully show that (1) level of education, health complaints, use of free time, family income, and also the number of dependents produce a significant influence in a simultaneous direction on the work participation of elderly people, (2) level of education, health complaints, family income with a partial direction producing a negative and significant influence, (3) the number of dependents with a partial direction producing a positive and significant influence, (4) using free time produces a significant influence. Thus, the large number of dependents is the most dominant variable that has an influence on the work participation of the elderly in Mengwi District, Badung Regency.